Mental health status of pregnant and breastfeeding women during the COVID‐19 pandemic: A call for action. Issue 1 (23rd July 2020) - Ceulemans, Michael; Hompes, Titia; Foulon, Veerle
Abstract : Increased prevalence of depressive symptoms and anxiety among pregnant women and women in the early postpartum period was observed during the lockdown in Belgium. Obstetricians must take actions to safeguard perinatal mental health.